Fracture of L2 with massive spinal epidural hematoma in a patient with ankylosing spondylitis - Chao, L.-Y.; Chou, C.-M.; Lien, F.-C.; Huang, Y.-H.; Chih, W.-H. (Osteologie, 2011)
It has been reported that even mild trauma may result in a fracture and a spinal epidural hematoma in patients with ankylosing spondylitis (AS). We herein presented a case of a patient with AS who sustained a fracture of L2 in an automobile accident and developed a massive spinal epidural hematoma.Findings The patient had few neurological symptoms until numbness and pain developed 50 hours after the initial trauma. T2-weighted magnetic resonance imaging showed an epidural hematoma over the posterior aspect of the spinal canal, reaching from T12 to L4. Posterior decompression surgery was performed. The neurological deficits resolved completely after the surgery.Conclusion Early surgical decompression of a massive epidural hematoma produced a favorable outcome in a patient with AS with neurological deficits.
Keywords: Ankylosing spondylitis; spinal epidural hematoma; surgical decompression; spinal fracture